Designing Study Protocol: The Effects of Rhythmic Maternal Movements on Motor Performance of Preterm Infants Hospitalized in a Neonatal Intensive Care Unit: A Randomized Controlled Clinical Trial - Aida Ravarian; Farin Soleimani; Nahid Rahmani; Firoozeh Sajedi; Moslem Shaabani; Mehdi Noroozi; Mohammad Mohseni-Bandpei (Mashhad University of Medical Sciences, 2024)
Background: The fetus receives various vestibular stimuli as a result of its mother's walking and other activities, while premature infants are deprived of these typical stimuli due to hospitalization in a neonatal intensive care unit (NICU).Methods: A single blinded randomized controlled clinical trial was designed to evaluate the effect of rhythmic maternal movements (RMM) on motor performance of infants born preterm with gestational age under 34 weeks. The aim of this plan is to stimulate the vestibular system in infants after preterm birth in hopes of improving motor performance. Seventy preterm infants will be randomized to experimental and control groups. The infants in the experimental group will be given RMM to improve motor development, heart rate and sao2. A neonatal occupational therapist trains mothers to do the RMM with a doll and explains the protocol. RMM is performed twice a day for a week. The Test of Infant Motor Performance (TIMP) is carried out at baseline and after a week of intervention by a blinded assessor.Discussion: This paper designed to study the effects of rhythmic maternal movements on motor performance, heart rate and sao2 of preterm infants hospitalized in a Neonatal Intensive Care Unit.